The Use of Mass Flux as a Risk Management Metric – Implementation at a DNAPL Site - Reynolds, David; Kirchner, Rachel; Rhodes, Stuart (Águas Subterrâneas, 2011)
Contaminated site investigations typically focus on chemical concentrations and subsurface flow processes at discrete locations, and then analysis of the data sets largely independent of each other. When both data types are considered, it is most often for the interpretation of plume dynamics. A growing trend is the combination of these data sets into a single quantitative measure of contaminant mass flux across a control plane. Mass flux has most often been used by practitioners to categorize a site when assessing source zone remediation techniques. Mass flux can also be used to estimate impacts on receptors, either in conjunction with, or as an alternative to point concentrations. The 1998 US EPA Monitored Natural Attenuation Seminar found that “flux estimates across the boundary to a receptor are the best estimate of loading to a receptor.” Mass flux is being used as a risk management metric at a DNAPL site in Western Australia owned by Argyle Diamonds. Mass flux across two control planes was measured using a number of methods before and after remediation. A Site Management Plan which uses the mass flux measured at the source zone as the metric by which human health and environmental values are protected (as opposed to point concentrations in monitoring wells) is under consideration by the regulatory body. This presentation outlines the methodology, and details key aspects which provide stakeholders confidence in the risk management at this unique site.